Faktor-Faktor Minat Mahasiswa Mengikuti Kegiatan Organisasi: Studi Deskriptif Di Pendidikan IPS FIS UNJ - Chintya Berliana; Abdul Haris Fatgehipon; Nandi Kurniawan (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
College Students' interest in participating in organizational activities is a current topic in the university environment. The existence of organizations can be seen from students' interest in joining organizations, one of which is in the Social Sciences Education Study Program, Faculty of Social Sciences, Jakarta State University. The aim of this research is to describe the factors of interest of Social Sciences Education Students in participating in organizational activities. This research uses a descriptive method with a qualitative approach. Data collection techniques were carried out using interviews, observation, questionnaires, documentation and literature study. The subjects in this research were students of the 2021-2022 Social Sciences Education study program. The research results show that most college students have an interest in organizational activities, and the internal factors for students joining an organization are: 1) having an open personality, 2) wanting to develop their interests and talents, 3) preparing themselves to enter the world of work. External factors for college students joining the organization are: 1) campus facilities, 2) friends in studying, 3) parents, 4) appreciation from friends and lecturers, 5) problems on campus. So it can be concluded that Social Sciences Education college students have an interest in participating in organizational activities. Several factors that determine a student's interest in joining an organization come from the student himself and also from the environment at the university.